Simple design modifications can tailor bat box thermal conditions to life history requirements in different habitats - George S. Bakken; Joy M. O'Keefe (Ecological Solutions and Evidence)
Abstract Artificial roosts (e.g. bat boxes) are widely used as surrogates for the large dead or damaged trees typically preferred by maternal female bats for pup rearing, but are also used by other life stages. Although roost temperature plays a critical role in promoting energy savings and increasing growth rates for pups, we lack rigorous data on how simple structural modifications and placement choices affect artificial roost temperatures. To obtain structural data, we tested modifications of the commonly used rocket box design with a simplified heat transfer analysis. Modifications varied box insulation, heat storage, colour, dimensions and orientations. We illustrate the results with plots of bat chamber temperatures for 3 consecutive days with representative weather combinations. Incorporating a layer of insulation above a heat storage layer stabilizes bat box internal temperatures. A water‐filled layer provides compact heat storage and locks internal temperature to ≥0°C until the water is frozen. In a sunny environment, the choice of box colour and orientation can reduce temperature extremes and stabilize temperatures (e.g. at low latitudes a flat box with an E‐W long axis and white south and west sides provided stable temperatures <40°C while other orientations did not). Box designs can also allow bats to select preferred temperatures, for example, by placing bat chambers both outside and inside an insulating or heat storage layer or increasing vertical temperature gradients with a taller box. Practical Implication. Our results and similar modelling will reduce effort by focusing field experiments on designs that are likely to satisfy bats' physiological requirements during key life history stages in varying habitats and possible future (warmer) climates.